Efficacy and safety of cutting therapy in the treatment of migraine: A protocol for systematic review and meta-analysis. Issue 50 (17th December 2021) - Guo, Wenping; Jin, Hongguang; Wang, Yiqiang; Zhu, Xing; Zhang, Guanwei; Wang, Te; Fan, Chunhui; Huang, Yongsheng
Abstract: Background: Migraine is a chronic paroxysmal neurovascular disease in which pain on one or both sides of the head is the main manifestation and is accompanied by other neurological manifestations. Clinical practice has shown that cutting therapy as a complementary alternative medicine can play a role in relieving migraine attacks. However, there is no consensus on the efficacy of cutting treatment in the treatment of migraine. The aim of this study was to conduct a meta-analysis to systematically evaluate the efficacy and safety of cutting therapy in the treatment of migraine. Methods: First, databases were searched for relevant literature. The main databases we searched were PubMed, the Web of Science, MEDLINE, Embase, Cochrane Library, the Chinese National Knowledge Infrastructure, the Chinese Science Journal Database, Wanfang Data, and the Chinese Biomedical Literature Database. The keywords searched were "cutting treatment, " " traditional Chinese medicine cutting treatment, " and "migraine." The search was conducted from inception to November 2021. Second, 2 reviewers independently completed the process of study selection, data extraction, risk of bias assessment and data synthesis in strict accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses Protocols statement guidelines. Finally, we will use Review Manager Version 5.3 software for meta-analysis. Results: This study will provide the most recent evidence related to the treatment of migraine by cutting therapy. Conclusion: The results of this systematic evaluation will provide an objective evidence-based framework for judging the effectiveness and safety of cutting therapy in the treatment of migraine.